Comprehensive Reproductive Health Education in Efforts to Prevent Sexual Violence - Eko Prabowo, Kukuh; Maria Sinaga, Riance; Yunia Wulandari, Shinta; Asmanovia, Rezi (BKM Public Health and Community Medicine, 2024)
Purpose: From 2018 to 2023, the number of reported violence cases against children in the Ministry of Women Empowerment and Child Protection's information system has increased from 11,401 cases in 2018 to 15,790 cases in 2023. Sexual violence is the most dominant form of violence experienced by children, ranging from 27.79% in 2020 to 60.37% in 2021 of total child violence cases. The most vulnerable age group is 13-17 years, with over 59% of victims in this age range each year. These increasing figures indicate that sexual violence prevention efforts are still not optimal. Despite the government's issuance of Permenag No. 73 of 2022 on the Prevention and Handling of Sexual Violence in Educational Units in the Ministry of Religion and the Ministry of Education, Culture, Research and Technology Regulation No. 46 of 2023 on the Prevention and Handling of Violence in Educational Environments, prevention remains inadequate. This paper aims to promote the implementation of comprehensive reproductive health education in schools. Content: School-based reproductive health education programs have proven crucial in enhancing information on sexual reproductive health and reducing risky sexual behaviors. These interventions not only improve knowledge, attitudes, and behaviors related to sexual health but also reduce the spread of misinformation from peers. Developing reproductive health education programs in schools should refer to existing guidelines and consider community backgrounds. Comprehensive reproductive health education is effective in improving knowledge, attitudes, and skills related to healthy relationships and preventing sexual violence against children. Additionally, this program enhances communication skills, literacy, and social-emotional learning. Therefore, it is essential for schools to adopt and integrate reproductive health education into their curriculum.